SIMULATION COMPONENT OF VIRTUAL MASS POLITICAL BEHAVIOUR IN RISK SOCIETY - Свідерська, О. І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The simulation component of the manifestation of virtual political behaviour in risk society is considered. It was determined that using social networks, a new reality, which serves dubbing of political life of the modern individual. An important aspect of the study is to take into account the role of virtualization of modern political behavior in a society full of risks of both man-made and natural nature, information overload, substitution of facts and post-truth. Political behaviour simulation component digital origin plays an important role in shaping not only its real manifestation, but also in the structure of political consciousness that leaves a mark on the subsequent policy actions or activity of the modern individual. Particularly dangerous is the integration of this component with a risk society in which risks are increasingly gaining enormous proportions. After all, manipulative technologies, which are conveniently used by politicians or individual government officials, have a powerful psychological impact on the consciousness of the modern individual. It is not just voters, which is constantly flowing information pile of dirt during the electoral manipulation, which is essentially situational. Rather, we are talking about an ordinary individual who in the 21st century is so imbued with false information and its constant flow that it is really difficult for him to distinguish the truth. In the end - for the individual truth has ceased to be a value. It is proved that the virtualization of political behaviour contributes to its simulation, which consists in the imaginary active participation in the political life or society. A separate component of such behaviour is the tendency of man to irrationalism, low resistance to manipulative influences on the one hand, and the active use of social networks by government elites to form appropriate political thinking and political behavior on the other.